(untitled) (Journal of Economic Research & Business Administration, 2025)
This article examines the development of mortgage lending in Kazakhstan, focusing on its dynamics and its relationship with key macroeconomic indicators. Special attention is given to the role of government programs and the integration of ESG (Environmental, Social, and Governance) principles to promote sustainability in the sector. While ESG standards are widely adopted in international financial systems, this study analyzes Kazakhstan’s unique economic and institutional context. Additionally, Uzbekistan is considered a country where certain effective financial and regulatory tools applied in Kazakhstan could potentially be adapted to local conditions. The analysis compares selected mortgage lending indicators between Kazakhstan and Uzbekistan and employs correlation and regression modeling to evaluate how macroeconomic variables such as GDP, interest rates, and the share of overdue loans impact mortgage lending volumes. Drawing on data from The Global Economy (2023), the study explores how mortgage programs in developed countries affect the ratio of banking sector assets to GDP, providing a global benchmark. A detailed analysis of mortgage trends from 2007 to 2023 reveals important patterns and correlations between macroeconomic factors and mortgage loan dynamics in both countries. Time series and correlation methods allowed the authors to establish statistically significant relationships, particularly in the case of Kazakhstan. As a result, a forecasting model was developed, incorporating GDP growth, lending interest rates, and the level of non-performing loans as independent variables. The article also discusses the integration of ESG standards into Kazakhstan’s mortgage finance system, highlighting their potential to foster green construction and sustainable housing development. These initiatives support broader sustainable development objectives and could be relevant for Uzbekistan as well. The authors argue that implementing green financial instruments such as green mortgages and funding programs for energy-efficient housing can reduce environmental harm and improve housing affordability in Kazakhstan, Uzbekistan, and other emerging economies. Key words: mortgage lending, sustainable development goals (SDGs), ESG standards, GDP, socio-economic development, Kazakhstan.